THE MEDICAL SIGNIFICANCE OF TICKS - PANNA LAL SAH (International Journal of Multidisciplinary Research and Studies, 2020)
Human Monocytic Ehrlichiosis (HME) is an emerging disease first described in 1987 and is transmitted by the bite of Amblyommaamericanum. Over the past 10 years, the CDC has documented increasing ehrlichiosis case reports nationwide. Our study site is a golf-oriented retirement community located in the Cumberland Plateau of Tennessee. In 1993, four men at the study site had symptoms consistent with HME which prompted a CDC outbreak investigation and led community managers to mitigate ticks feeding on deer. The objectives of this study were to measure the efficacy of current tick mitigation attempts, to determine the level of infection and composition of tick-borne disease in the study area, and to assess which wildlife species are potentially acting as reservoirs for disease. Ticks were sampled in the community at eight sites of ‗4-poster‘ acaricide applicator utilization and at seven untreated sites. Close to the ‗4-poster‘ devices, larval, nymphal, and adult tick abundances were reduced by 90%, 68% and 49% respectively (larval p< 0.001, nymphal p< 0.001, adult p=0.005) relative to the untreated areas. We extracted DNA from A. americanum ticks collected at the treatment and non-treatment sites and tested for Ehrlichia spp. infections. Of 253 adult and nymphal A. americanum tested, we found 1.2% to be positive for Ehrlichiachaffeensis, 4.7% positive for Ehrlichiaewingii, and 1.6% positive for Panola Mountain Ehrlichia; in combination this prevalence is similar to that reported in other Ehrlichia-endemic areas of the eastern U.S.. We also performed blood meal analysis on DNA from A. americanum ticks and the results suggest that the most significant reservoir hosts for Ehrlichia spp. are white-tailed deer, turkeys, grey squirrels, and Passeriformes.